Non-communicable disease (NCD) corners in public sector health facilities in Bangladesh: A qualitative study assessing challenges and opportunities for improving NCD services at the primary healthcare level - Rawal, Lal B; Kanda, Kie; Biswas, Tuhin; Tanim, Md. Imtiaz; Poudel, Prakash; Renzaho, Andre M N; Abdullah, Abu S; Shariful Islam, Sheikh Mohammed; Ahmed, Syed Masud (BMJ Journals, 2022)
This article was published in The BMJ Open [ © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-029562. The Journal's website is at: https://bmjopen.bmj.com/content/9/10/e029562